POLYNOMIAL SOLUTIONS OF ALGEBRAIC ORDINARY DIFFERENTIAL EQUATIONS. I - Gorbuzov, V. N. (Matematichki Bilten, 1993)
Polynomial solutions with singular and non-singular degrees of algebraic differential equations are considered.